Regenerative Medicine Approaches in COVID -19 Pneumonia - Asgharzad, Samira; Alizadeh, Akram; Arab, Samaneh (Current stem cell research & therapy, 2021)
Regenerative medicine (RM) is an interdisciplinary field that uses different approaches to accelerate the repair and regeneration or replace damaged or diseased human cells or tissues to achieve normal tissue function. These approaches include the stimulation of the body's own repair processes, transplantation of progenitor cells, stem cells, or tissues, as well as the use of cells and exosomes as delivery-vehicles for cytokines, genes, or other therapeutic agents. COVID-19 pneumonia is a specific disease consistent with diffuse alveolar damage resulting in severe hypoxemia. Therefore, the most serious cause of death from COVID-19 is lung dysfunction. Here, we consider RM approaches to cure COVID-19 pneumonia based on what RM has so far used to treat lung diseases, injuries, or pneumonia induced by other pathogens. These approaches include stem and progenitor cell transplantation, stem cell-derived exosomes, and microRNAs therapy.